OPTIMALISASI PEMBELAJARAN SENI BUDAYA DAN PRAKARYA (SBDP) MELALUI PROJECT BASED LEARNING BERBASIS TIKTOK DI KELAS IV SD NEGERI 6 SUAK TAPEH - Arsi Tri Amanda; Mgs Firdaus; Yusni Arni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Project Based Learning (PJBL)model integrated with the TikTok application on student learning outcomes in thesubject of Arts, Culture, and Crafts (SBDP) for Grade IV students at SD Negeri 6Suak Tapeh. The research was motivated by low student participation andachievement in SBDP learning, particularly in visual arts. The research methodused was quantitative with a quasi-experimental approach and a nonequivalentcontrol group design. The sample consisted of two classes: the experimental class(using PJBL with TikTok integration) and the control class (using conventionalmethods). Data were collected through pretests and posttests in the form of essayquestions. The analysis showed a significant difference between the posttestresults of the two classes, with an average posttest score of 86.11 in theexperimental class and 40.80 in the control class. The t-test results showed asignificance value of 0.000 < 0.05), indicating that the application of PJBL withTikTok had a significant impact on improving student learning outcomes. Thestudy concludes that the PJBL model based on TikTok is effective in optimizingSBDP learning by increasing active participation, creativity, and students'understanding of the material.